Problematika Penerapan Kurikulum Merdeka Pada Pembelajaran Pendidikan Agama Islam Di SD Islam Ihsan Al-Baity Desa Berenge Kecamatan Janapria: Problems of Implementing the Independent Curriculum in Islamic Religious Education and Character Education Learning at SDI Ihsan Al-Baity, Berenge Village, Janapria District - Muhammad Hanafi (Pendidikan Al-Gafari, 2026)
The independent learning curriculum is defined as a learning plan that provides students with the opportunity to learn in a relaxed, calm, stress-free, and joyful manner, while taking into account the natural talents of the students. This study aims to identify the challenges in implementing the Independent Curriculum in Islamic Religious Education (PAI) and Character Education (Budi Pekerti) at Ihsan Al-Baity Islamic Elementary School, Berenga Village, Janapria District. This study used qualitative methods with data collection techniques through observation, interviews, and documentation. The results of the study indicate that challenges in implementing the Independent Curriculum in Islamic Religious Education (PAI) and Character Education (Budi Pekerti) at Ihsan Al-Baity Islamic Elementary School include limited resources, teacher skills that still need to be improved, and parental involvement that still needs to be improved. This research is expected to contribute to the development of education at Ihsan Al-Baity Islamic Elementary School and other schools in Berenga Village, Janapria District.